Reinforcement of polyether polyurethane with dopamine-modified clay : the role of interfacial hydrogen bonding - Phua, Si Lei (2013)
Dopamine-modified clay (D-clay) was successfully dispersed into polyether polyurethane (PU) by solvent blending. It is found that the incorporation of D-clay into PU gives rise to significant improvements in mechanical properties, including initial modulus, tensile strength, and ultimate elongation, at a very low clay loading. The large reinforcement could be attributed to the hydrogen bonds between the hard segments of PU and stiff D-clay layers that lead to more effective interfacial stress transfer between the polymer and D-clay. Besides, the interactions between D-clay and PU are also stronger than those between Cloisite 30B organoclay and the PU chains. Consequently, at a similar clay loading, the PU/D-clay nanocomposite has much higher storage modulus than the PU/organoclay nanocomposite at elevated temperatures.